2014
DOI: 10.1007/s13238-014-0087-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of SCARB2-mediated attachment and uncoating of EV71

Abstract: Unlike the well-established picture for the entry of enveloped viruses, the mechanism of cellular entry of non-enveloped eukaryotic viruses remains largely mysterious. Picornaviruses are representative models for such viruses, and initiate this entry process by their functional receptors. Here we present the structural and functional studies of SCARB2, a functional receptor of the important human enterovirus 71 (EV71). SCARB2 is responsible for attachment as well as uncoating of EV71. Differences in the struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
99
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 49 publications
6
99
0
6
Order By: Relevance
“…It was recently suggested that the canyon region of EV71 mediates its interaction with SCARB2 (18). Specifically, five synthetic peptides whose sequences were located around the canyon, according to the three-dimensional structure of EV71, including VP1-2 (residues 92 to 106), VP1-6 (residues 212 to 225), VP1-8 (residues 280 to 293), VP2-2 (residues 136 to 150), and VP3-4 (residues 175 to 188), were found to bind SCARB2 in pulldown assays (18) (Fig. 2E).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently suggested that the canyon region of EV71 mediates its interaction with SCARB2 (18). Specifically, five synthetic peptides whose sequences were located around the canyon, according to the three-dimensional structure of EV71, including VP1-2 (residues 92 to 106), VP1-6 (residues 212 to 225), VP1-8 (residues 280 to 293), VP2-2 (residues 136 to 150), and VP3-4 (residues 175 to 188), were found to bind SCARB2 in pulldown assays (18) (Fig. 2E).…”
Section: Discussionmentioning
confidence: 99%
“…RNA (10,18). PSGL-1 facilitates virus infection of leukocytes in a strain-specific manner (19,20); however, its exact role in viral entry in nonleukocytes remains unclear.…”
mentioning
confidence: 99%
“…In this study we show that alterations in helix 5 but not in helix 7 induce the fragmentation of LIMP-2. These helices are part of a helical bundle mainly formed by the three a-helices 4, 5 and 7 [2] composing the ligand binding site of LIMP-2 for interaction with GC [2] or enteroviruses [32]. It has been proposed that the helical bundle adopts two different pH-dependent conformations [33].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous crystal structure of unenveloped HAV (7) showed no trace of the canyon that encircles the fivefold axes of enteroviruses and is often the site of receptor binding (8,9). Indeed, the structure provided no clues as to where T-cell Ig and mucin 1 (TIM-1), the proposed receptor (10,11), might attach.…”
mentioning
confidence: 95%